问题 解答题
化简求值
(1)(9a2-12ab+5b2)-(7a2+12ab+7b2),其中a=
1
2
,b=
1
2

(2)已知|x+2|+(3x-2)2=0,求
1
2
x-2(x-
1
3
y2)+(-
3
2
x+
1
3
y2)
的值.
答案

(1)原式=9a2-12ab+5b2-7a2-12ab-7b2

=(9-7)a2+(-12-12)ab+(5-7)b2

=2a2-24ab-2b2

当中a=

1
2
,b=
1
2
时,

原式=2×(

1
2
2-24×
1
2
×
1
2
-2×(
1
2
2

=2×

1
4
-6-
1
2

=

1
2
-6-
1
2

=-6.

(2)∵|x+2|+(3x-2)2=0,

∴x+2=0,3y-2=0,

∴x=-2,y=

2
3

原式=

1
2
x-2x+
2
3
y2-
3
2
x+
1
3
y2

=(

1
2
-2-
3
2
)x+(
2
3
+
1
3
)y2

=-3x+y2

当x=-2,y=

2
3
时,

原式=-3×(-2)+(

2
3
2

=6+

4
9

=6

4
9

问答题 简答题
单项选择题